DO FUNDAMENTAL INDEXES PRODUCE HIGHER RISK-ADJUSTED RETURNS THAN MARKET CAP INDEXES? EVIDENCE FOR CHINESE STOCK MARKET - Bizhanova, Madina; Gabayev, Asker (Nazarbayev University Graduate School of Business, 2023)
The proponents of fundamental indexing (‘FI’) theorize that a traditional value weighted portfolio is characterized by a return drag due to overweighting overvalued stocks and underweighting undervalued stocks. A number of empirical studies found an extra return for an FI strategy compared to a value weighted benchmark. However, the critics argue that the primary driver of FI’s superior performances reflects not the drag avoided but a style shift towards value strategy. Hence the analytical comparison of an FI alternative should control for a style shift when testing for the drag effect. The 2018 study of an FI strategy for the U.S. stock market by De Moor, Liu & Sercu employs a vigintile portfolio analysis to control for style shift and do not find any economically or statistically significant benefit from drag avoidance. I employ the conventional factor analysis and the proposed double-sorted bucket analysis to test the FI strategy using Chinese stock market data. Like others before, I conclude that the FI’s extra return is primarily due to its value bias rather than avoidance of the drag effect.
Keywords: type of access: gated access